﻿Development and validation of analytical procedure for analysis of Amoxiciline, Metronidazole and Omeprazole, used as anti- Helicobacter pylori agents alone and in mixture - Vania Maslarska; Lily Peikova; Maya Georgieva; Stefka Ivanova; Miglena Smerikarova; Stefan Balkanski; Stanislav Bozhanov (Pensoft Publishers, 2023)
Background: The contemporary treatment of ulcerogenic diseases and gastroesophageal reflux disease is related usually to application of a combination of imidazole-based antibacterial, antibiotic and proton pump inhibitor. In the current study, the three most common representatives Amoxicilline (AMO), Metronidazole (MET) and Omeprazole (OME), respectively, are subjected to analysis through classical analytical procedure, providing high level accuracy, sensitivity and good separation abilities. As such a UV/VIS method was applied as a well known identification and quantitation technique for analyses in various samples. Furthermore, this technique is known to be a good detection method in combination with chromatographic systems. Purpose: A simple, specific, accurate and precise reverse phase-high performance liquid chromatographic method has been developed for the simultaneous determination of Amoxicillin Trihydrate (AMO), Metronidazole (MET) and Omeprazole (OME) in synthetic mixture. Materials and methods: Some important parameters like pH of the mobile phase, concentration of the acid or buffer solution, percentage and type of the organic modifier, etc. were tested for a good chromatographic separation. The sample was analyzed using a mobile phase of Acetonitrile: Phosphate buffer (pH=7.6±0.1) (40:60 v/v). The flow rate was 1.0 mL/ min with detection at 280 nm. Results: The retention time for AMO, MET and OME was found to be 1.67, 2.86 and 5.99 min respectively, and the recoveries in the synthetic mixture were between 98 and 102%. The validated method was linear over the concentration range of 25 to 200 μg/mL for AMO, 12.5 to 100 μg/mL for MET and 5-40 µg/mL for OME, with a correlation coefficient > 0.999. Conclusion: The developed method has been validated in accordance with the International Conference on Harmonization (ICH) guidelines and showed excellent linearity, accuracy, precision, specificity, robustness, as well as system suitability results within the acceptance criteria.